Implementasi Metode ELECTRE dalam Sistem Pendukung Keputusan Penentuan Kelayakan Pinjaman - I Putu Gede Abdi Sudiatmika; I Made Agus Widiana Putra; I Made Agus Oka Gunawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
XYZ Cooperative is engaged in credit business by providing loans to its members. Loan activities provided by the XYZ Cooperative, members can borrow and return money guaranteed by mutual agreement between the management of the cooperative and the borrower without having to pay fines when late in making installment payments. The problem that occurs in determining loan eligibility at the XYZ Cooperative is that the assessment in determining loan eligibility still only gives a decision whether or not a loan is appropriate, without taking into account the percentage value of loan eligibility. The decision support system is an alternative in determining a decision making that can produce solutions to assist cooperatives in determining eligibility more quickly. In determining the eligibility to provide loans to members using the decision-making method, namely the ELECTRE Method. There are 5 stages in this study, namely Data Collection, Criteria and Weight Analysis, Electree Method Calculations, System Implementation, and System Testing. As for this study using 6 criteria, namely collateral, income, loan amount, installments, active members and age. The results of testing the system using the blackbox testing method, which shows that the system built is capable of running well and producing output according to the design. And for the results of the comparison of the results of calculations on the system and the results of manual calculations, it is found that the results of the Electre method calculations have obtained the same results.